Les mobilités internes en Tunisie depuis la fin des années 1990 : une dynamique géographique à différentes échelles - Hajer Ben Hamza; France Guérin-Pace (EchoGéo)
This article looks at internal migration in Tunisia around the year 2011. Using the 2014 census and a general population survey (ETST, 2016), it outlines a geography of recent Tunisian mobility. Besides the long-standing regional inequalities between coastal and peripheral regions, it shows the contrasts that have emerged at different scales of the Tunisian territory. A distinctive feature of the internal mobility following the events of 2011, which the census does not capture, is that the movements seem largely temporary, as captured by the ETST survey.